Pembentukan Karakter Kepemimpinan Siswa Kelas X Me-lalui Mata Pelajaran Sejarah Kebudayaan Islam di MAN 1 Kabupaten Bogor - Nabila El Atikah; Fahmi Irfani; Nirwan Syafrin (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
This study aims to determine the formation of student leadership characters through the subjects of Islamic cultural history at MAN 1 Bogor Regency. The method used in this research is a survey method with a quantitative approach. The sample in this study was 40% of the total population of 150 students of class X (60 respondents) using simple random sampling technique. Data collection techniques using observation, questionnaires (questionnaires) and documentation. In the validity test of the 20 items, there are 18 questions that are proven valid and the reliability test results of the coefficient of 0.703 are declared reliable. Analyst requirements test is done by linearity test and normality test. Data analysis used the product moment correlation technique and after calculating the Pearson correlation, the rxy yield was 0.817 at an index of 0.80-1,000, which means that there is a strong correlation between the formation of student leadership characters and the history of Islamic culture at MAN 1, Bogor Regency. The results of the study were indicated by the tcount value of 10,658 and the ttable was found to be 1,672. So the conclusion is that tcount > ttable (10,658 > 1,672). If tcount > ttable then Ho is rejected, meaning that it is statistically significant, from the results of the t test a significant value less than 0.05 (0.000 < 0.05) means that there is a significant relationship between the formation of leadership character in class X students and the subject of cultural history. Islam. Keywords: Character, Leadership, History of Islamic Culture